Controllable emulsion phase behaviour via the selective host-guest recognition of mixed surfactants at the water/octane interface. (20th July 2019) - Jia, Han; Leng, Xu; Wang, Qiuxia; Han, Yugui; Wang, Shaoyan; Ma, An; Guo, Muzhi; Yan, Hui; Lv, Kaihe
Graphical abstract: Highlights: The additional β-CD could further reduce the IFT in mixed surfactant system. Low concentration of β-CD promotes the formation and stability of O/W emulsions. Emulsion phase inversion is induced by moderate β-CD. Inclusion complexes may compete with surfactants at interface with excess β-CD. Abstract: Emulsions are deeply involved in almost all aspects of the petroleum industry, especially in enhanced oil recovery. Supramolecular chemistry proposes a facile and controllable method to construct target assemblies. In this report, we investigated the effects of β-cyclodextrin (β-CD) on the emulsions stabilized by the mixed N -dodecyl- N -methylpyrrolidinium bromide (L12) and sodium dodecyl sulfate (SDS). The additional β-CD exerted strong influences on the water/ n -octane interfacial tension (IFT) between n -octane and the mixed L12/SDS aqueous solutions, which should be attributed to its selective host-guest recognition. Interestingly, the additional β-CD in moderate concentrations could selectively remove the major surfactant molecules at the interface to adjust the hydrophilic-lipophilic balance of the mixed adsorption layers, thereby causing the transformation of the emulsion type from O/W to W/O. The addition of excess β-CD would generate the construction of n -octane/β-CD complexes to enhance the hydrophilicity of the interfacial layers, which leads again to phase inversion. Emulsions and their types were characterized and confirmed by the measurements of their conductivities, average droplet radii and rheological properties. To verify the proposed mechanism for the multiple phase inversion, the effects of L12/SDS molar ratios and β-CD concentrations were studied in depth in the control experiments.